pengaruh penggunaan media maket dengan metode inkuiri terhadap pemahaman konsep siswa di smps advent nusra noelbaki tahun ajaran 2018/2019 - Ariesta Mudi; theodora S.N Manu (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2019)
Abstract This research is aimed at knowing the influence of using “Maket” media with Inquiry method towards students’ understanding on Biological concepts. The research method used in this research was experimental with One Group Pretest-Postest Design. The population of this study 37 students of grade VII in SMPS Advent Nusra Noelbaki. The sampling technique used in this study was Purposive Sampling; Since the number of population was too small, the writer took them all as sample of this study, as treatment group. From this study, the data obtained by test, it is essay test, then the data were analyzed used t-test analysis. From the data analysis, it was shown that tcount = 6,514 and ttable = 2,056 with the significant level (a) = 0,05. Since the result of tcount = 6,514 ˃ ttable = 2,056, therefore the null hypothesis (Ho) is rejected and Alternative hypothesis (Ha) is accepted. It is conluded that there is an influence on the use of “Maket” media with inquiry method toward students’ understanding on Biology concepts. The teaching and learning process using “Maket” media with Inquiry method made students more active, the teaching and learning is not monotonous and the students are more attractive participate and more understand the material taught. Key Words:“Maket” Media, Inquiry Method, Concept Understanding